Analysis of the Power Flow of the Gorontalo Electricity System Due to the Entry of 150 KV Industrial Customers - Ismail, Ilham; Surusa, Frengki Eka Putra; Humena, Steven (Jambura Journal of Electrical and Electronics Engineering, 2024)
Currently, in Pohuwato Regency, Popayato District, a wood pellet industry factory has been built by PT. Biomass Jaya Abadi (BJA). To meet electricity needs, electrical energy is taken from the PLN electricity supply through a 150 kV high-voltage electricity network and a special substation (GI) is made to serve its electrical energy needs. So it is said to be a high voltage customer. As a result of the entry of these high voltage customers, it will affect the configuration of the existing electrical system. The purpose of this study was to determine the value of voltage, load flow and power losses after the entry of 150 kV high voltage industrial customers. The method used in this study is the Newton Rhapson method with the help of ETAP 19.01 software. From the simulation results with the inclusion of PT. The BJA can improve the voltage profile on each bus of the 150 kV Gorontalo electrical system and 20 kV outgoing. Loss of power loss after the entry of PT. BJA can provide very small comparison percentages. So that it can provide better system capabilities.